Gastric Acid Suppressant Prophylaxis in Pediatric Intensive Care. Issue 7 (September 2015) - Costarino, Andrew T.; Dai, Dingwei; Feng, Rui; Feudtner, Chris; Guevara, James P.
<x xml:space="preserve">Abstract</x> Objectives: Stress-related gastrointestinal bleeding may occur in PICU patients. Raising gastric pH with acid suppressant medications is the accepted treatment. We describe the use of histamine 2 receptor blockers and proton pump inhibitors and associated factors among a national sample of PICU patients. Design: Retrospective cohort analysis using Pediatric Health Information System clinically detailed administrative database. Setting: Forty-two children's hospitals throughout the United States. Patients: All hospitalizations for all patients 20 years old or younger, admitted directly to a PICU, from January 1, 2007, through December 31, 2011. Interventions: None. Measurements and Main Results: The exposure of interest was treatment with a histamine 2 receptor blocker, proton pump inhibitor, or both on the first day of PICU admission. Demographics, principal and additional diagnoses, and procedure codes were assessed. For each hospitalization, principal diagnosis, coagulation disorder, head trauma, spinal trauma, severe burns, sepsis, gastrointestinal hemorrhage, mechanical ventilation, blood product transfusion, and 10 complex chronic conditions were identified. The frequency of principal diagnoses was determined to identify the most prevalent PICU diseases. Acid suppressant use was categorized as high or low. Three hundred and thirty-six thousand ten inpatient hospitalizations were sampled. Histamine 2 receptor blocker or proton pump inhibitor was used in 60.0%, with histamine 2 receptor blocker alone in 70.4%, proton pump inhibitor alone in 17.8%, and both agents in 11.8%. Use increased over the sample years 2007 through 2011. Gastrointestinal bleeding occurred in 1.32% of hospitalizations with transfusion needed in 0.1%. Among most prevalent diagnoses, histamine 2 receptor blocker and proton pump inhibitor use ranged from 33% to 87%. Sepsis, coagulopathy, and mechanical ventilation identified higher use. Use of histamine 2 receptor blocker or proton pump inhibitor among hospitals varied considerably ranging from 28% to 87%. Conclusions: Histamine 2 receptor blocker and proton pump inhibitor are prescribed in most PICU patients, but significant variation exists across health conditions and hospitals. Institutional preferences likely influence variation. Gastrointestinal hemorrhage is infrequent in the current era. Study data limitations prevent examination of associations between medication use and patient outcomes.